Hubungan Dukungan Keluarga dengan Self-Care Management pada Penderita Hiv/Aids (ODHA) di Puskesmas Bergas: The Relationship Between Family Support and Self-Care Management in HIV/AIDS Patients (ODHA) at Bergas Community Health Center - Luluk Sri Nurhalizha; Liyanovitasari (Journal of Holistics and Health Sciences, 2026)
Self-care management is the ability of people living with HIV/AIDS (PLWHA) to manage their health independently through adherence to ARV therapy, health decision-making, adoption of a healthy lifestyle, and daily condition monitoring. This ability is important for maintaining immune status, preventing complications, and improving quality of life during long-term treatment. Its implementation is influenced by external factors, especially family support, which helps PLWHA cope with physical, psychological, and social problems, thereby contributing to the success of self-care management. This study aims to determine the relationship between family support and self-care management in PLWHA. This study used a quantitative method with a correlational descriptive design through a cross-sectional approach. The population consisted of all HIV/AIDS patients undergoing ARV therapy, with a sample of 144 respondents using total sampling technique. The instruments used were the family support questionnaire (MSPSS Family) and self-care management. Data analysis was performed univariately and bivariately using Spearman Rank correlation test. The results showed that most respondents had high levels of family support (130 respondents, 90.3%) and high levels of self-care management (135 respondents, 93.8%). Bivariate analysis showed a significant relationship between  family support and self-care management in HIV/AIDS patients at the Bergas Community Health Center with a p-value < 0.001 and a correlation coefficient of r = 0.762. Family support plays an important role in improving the ability of PLWHA to manage their own self-care. Therefore, family involvement in PLWHA service and assistance programs is necessary to improve the success of self-care management and the quality of life of patients. ABSTRAK Self-care management adalah kemampuan penderita HIV/AIDS (ODHA) dalam mengelola kesehatannya secara mandiri melalui kepatuhan terapi ARV, pengambilan keputusan kesehatan, penerapan gaya hidup sehat, dan pemantauan kondisi harian. Kemampuan ini penting untuk menjaga status imun, mencegah komplikasi, dan meningkatkan kualitas hidup selama pengobatan jangka panjang. Pelaksanaannya dipengaruhi faktor eksternal, terutama dukungan keluarga, yang membantu ODHA menghadapi masalah fisik, psikologis, dan sosial sehingga berperan dalam keberhasilan self care management. Penelitian ini bertujuan mengetahui hubungan antara dukungan keluarga dengan Self-care management pada ODHA. Penelitian ini menggunakan metode kuantitatif dengan desain deskriptif korelasional melalui pendekatan Cross Sectional. Populasi adalah seluruh penderita HIV/AIDS yang menjalani terapi ARV, dengan sampel 144 responden menggunakan teknik total sampling. Instrumen yang digunakan yaitu kuesioner dukungan keluarga (MSPSS Family) dan self care management. Analisis data dilakukan secara univariat dan bivariat menggunakan uji korelasi Spearman Rank. Hasil penelitian menunjukkan bahwa sebagian besar responden memiliki dukungan keluarga dalam kategori tinggi sebanyak 130 responden (90,3%) dan self care management dalam kategori tinggi sebanyak 135 responden (93,8%). Analisis bivariat menunjukkan terdapat hubungan yang signifikan antara dukungan keluarga dengan self-care management pada penderita HIV/AIDS di Puskesmas Bergas dengan nilai p-value 0,001 dan koefisien korelasi r = 0,762.  Dukungan keluarga memiliki peran penting dalam meningkatkan kemampuan ODHA dalam mengelola perawatan diri secara mandiri. Oleh karena itu, diperlukan keterlibatan keluarga dalam program pelayanan dan pendampingan ODHA untuk meningkatkan keberhasilan self-care management dan kualitas hidup penderita.